Beyond polarisation: reimagining communities through the imperfect act of ontologising. Issue 1 (2nd January 2022) - Huybrechts, Liesbeth; Devisch, Oswald; Tassinari, Virginia
ABSTRACT: In participatory design (PD) processes driven by institutions, designers struggle in reaching out to silent and/or silenced human and more-than-human voices within local communities. This can in a long run contribute to polarisation in the design process. This paper explores how to reimagine designing with communities beyond polarisation, by rethinking the PD practice of 'infrastructuring' (i.e. 'commoning' and 'institutioning') from within the perspective of the ontological turn. This process of 'ontologising' infrastructuring aims to enable designers to design with and for radical interdependence and reach out to (ontologically) diverse actors who might in first instance seem unrelated if not antagonistic. We situate and evaluate this process in a concrete case study in urban planning in the Low Countries where we used mappings and platforms to map and engage with radical interdependencies. Rather than crystallising 'ontologising' as a PD practice, in this paper we aim to foreground it as a set of capabilities that designers may use to steer and evaluate their PD process with close attention to its politics.